Penerapan Nilai Disiplin Melalui Kegiatan Sholat Dhuha di MI Islamiyah Palangka Raya - Sufiyatun Sufiyatun (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Discipline is one of the important values in the world of education that contributes to the order and responsibility of students in academic and social life. This study aims to analyze the implementation of discipline values through Dhuha prayer activities at MI Islamiyah Palangka Raya. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. The results of the study show that Dhuha prayer plays a role in shaping student discipline, which is reflected in the habit of coming on time, regularity in worship, compliance with rules, and politeness and courtesy. In addition, this activity increases students' mental readiness in learning, making them more focused, patient, and enthusiastic in facing academic tasks. The role of teachers as role models and mentors is very influential in the success of this program, supported by the involvement of parents who ensure that students participate in activities consistently. Synergy between schools, teachers, and parents contributes to the sustainability of the program, so that disciplinary values can be effectively instilled. Thus, Dhuha prayer not only functions as worship, but also becomes a means of forming the discipline character of students who are responsible and have a high work ethic.